Low seroprevalence of Murray Valley Encephalitis and Kunjin viruses in an opportunistic serosurvey, Victoria 2011 - Williams, Stephanie; Richards, Jack; Faddy, Helen; Leydon, Jennie; Moran, Rodney; Nicholson, Suellen; Perry, Faye; Paskin, Roger; Catton, Mike; Lester, Rosemary; MacKenzie, John (Wiley-Blackwell Publishing Asia, 2013)
Objective: To assess evidence of recent and past exposure to Murray Valley encephalitis virus (MVEV) and West Nile clade Kunjin virus (KUNV) in residents of the Murray Valley, Victoria, during a period of demonstrated activity of both viruses in early 2011. Methods: A cross-sectional serosurvey using two convenience samples: stored serum specimens from a diagnostic laboratory in Mildura and blood donors from the Murray Valley region. Specimens were collected between April and July 2011. The main outcome measure was total antibody (IgM and IgG) reactivity against MVEV and KUNV measured using an enzyme immunoassay and defined as inhibiting binding of monoclonal antibodies by >50%, when compared to negative controls. Evidence of recent exposure was measured by the presence of MVEV and KUNV IgM detected by immunofluorescence. Results: Of 1,115 specimens, 24 (2.2%,95% CI 1.3-3.0%) were positive for MVEV total antibody, and all were negative for MVEV IgM. Of 1,116 specimens, 34 (3.1%, 95% CI 2.0-4.0%) were positive for KUNV total antibody, and 3 (0.27%) were KUNV IgM positive. Total antibody seroprevalence for both viruses was higher in residents born before 1974. Conclusions: Despite widespread MVEV and KUNV activity in early 2011, this study found that seroprevalence of antibodies to both viruses was low (<5%) and little evidence of recent exposure. Implications: Our findings suggest both viruses remain epizootic in the region and local residents remain potentially susceptible to future outbreaks.